Very high cycle fatigue on gas metal arc butt-welded AA6061-T6 plates - Kim, Iksu; Lee, Moon G.; Jun, Martin Byung Guk; Cho, Jungho; Jeon, Yongho (Journal of Mechanical Science and Technology, 2023)
In the automobile industry, there is a push to maximize the mileage of electric vehicles by using lightweight materials. Hence, the use of welded aluminum in electric vehicles is increasing, and there is a clear need for detailed characterization of the fatigue life of these welded parts. In this study, gas metal arc welded AA6061-T6 specimens were fabricated and an ultrasonic fatigue test method for ultra-high cycle fatigue testing was proposed. An S-N fatigue test curve of 109 cycles was obtained, with an infinite life (109 cycles) confirmed at 118 MPa and 105 cycle level fatigue life confirmed at 216 MPa.
Keywords: AA 6061-t6; AA6061-T6; Fatigue test method; Gas metal arcs; Gas metal-arc welding; Lightweight materials; Plate specimen; Ultra-high; Ultrasonic fatigue tests; Very-High-Cycle Fatigue; AA 6061-T6; Butt welding; Gas metal arc welding; Plate specimen; Ultrasonic fatigue test; Very high cycle fatigue